2021
DOI: 10.1123/ijspp.2020-0387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Presession Well-Being Perception on Internal Training Load in Female Volleyball Players

Abstract: Purpose: To evaluate if the internal training load (ITL; Edwards heart rate [HR]-based and session-rating of perceived exertion [RPE] methods) is affected by the presession well-being perception, age, and position in elite (ie, Serie A2) female volleyball training. Methods: Twelve female elite volleyball players (age: 22 [4] y, height: 1.80 [0.06] m, body mass: 74.1 [4.3] kg) were monitored using an HR monitor during 32 team training sessions (duration: 1:36:12 [0:22:24], in h:min:s). Linear mixed-effects mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In volleyball, the different tasks of athletes on the court can influence the individual demands of each athlete [ 38 , 49 , 54 , 55 ]. Thus, to understand this difference, all analyses of training intensity were performed by separating athletes by playing position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In volleyball, the different tasks of athletes on the court can influence the individual demands of each athlete [ 38 , 49 , 54 , 55 ]. Thus, to understand this difference, all analyses of training intensity were performed by separating athletes by playing position.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the external training intensity in Italian elite female volleyball athletes, Ungureanu et al [55] showed that S and MB performed the highest occurrence of jumps in training compared to hitters and opposites. In another study on women's collegiate volleyball players in different playing positions using an accelerometer, Kupperman et al [49] demonstrated that the setter accumulated the most jumps of any position in matches and performed three times as many medium jumps in training sessions than in matches.…”
Section: Training Intensity In the Different Microcycles According To...mentioning
confidence: 99%
“…Also, there are a lot of studies that investigate the training methods to improve performance in the literature [6,8]. Different training monitoring and testing methods are used to evaluate the performance of the players in volleyball [9,10]. One of these evaluation methods is jump height measurement.…”
Section: Introductionmentioning
confidence: 99%
“…While this evidence is important from a practical standpoint to identify the main match load measures affecting post-match perceived well-being [5], the assessment of the relationships between pre-match well-being and match loads could also provide further insight for women's rugby sevens practitioners about players' capacity to perform matches based on previous well-being values. Previous studies across various team sports mainly assessed the effect of well-being on training sessions rather than on match performance [15][16][17][18][19]. Specifically, a negative effect of pre-training perceived well-being on external load measures in Australian football players [15] and on internal perceived training load in professional male soccer [16] as well as female volleyball players [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies across various team sports mainly assessed the effect of well-being on training sessions rather than on match performance [15][16][17][18][19]. Specifically, a negative effect of pre-training perceived well-being on external load measures in Australian football players [15] and on internal perceived training load in professional male soccer [16] as well as female volleyball players [19]. Moreover, significant, although trivial, relationships were found between pre-training well-being and subsequent training load in American college football players [17].…”
Section: Discussionmentioning
confidence: 99%